2016
DOI: 10.1039/c6cc08187h
|View full text |Cite
|
Sign up to set email alerts
|

One-step fabrication of porous oxygen-doped g-C3N4with feeble nitrogen vacancies for enhanced photocatalytic performance

Abstract: Porous oxygen-doped graphitic carbon nitride (g-CN) with feeble nitrogen vacancies was fabricated through thermal polycondensation of melamine with an appropriate amount of polyvinylpyrrolidone. After optimization, the bandgap of g-CN can be narrowed by 0.2 eV and the specific surface area expanded, which contribute to increasing the utilization of solar energy. Consequently, the optimized g-CN exhibits impressive enhancement in photocatalytic hydrogen evolution performance, by nearly 5 times compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 30 publications
(33 reference statements)
1
27
0
Order By: Relevance
“…[29] Specifically,t he value of N (2C) /N (3C) in the RCN was only 0.2 lower than that of g-C 3 N 4 ,w hereasR CNO displayed av alue that was 1.00 lower;t his indicated that the pre-oxygenated treatment towards the g-C 3 N 4 prefers much the nitrogen vacancies formation during the H 2 reduction step, which was Table 2). The XPS spectra of O1s in g-C 3 N 4 andR CN showed a peak at the binding energy of 531.85 eV,w hich was attributed to the Oa toms in the NÀCÀOÀHm oiety.T he O1s peak in the RCNO sample was shifted to al ower binding energy of 531.36 eV,w hich corresponds to the formation of the C (3C) ÀNÀ Of unctionalg roup; [26] furthermore,anew peak appeared at 533.28 eV,w hich represented the Oa tom in C=Oo rC ÀO groups [30] and should be relatedt ot he release of the Na tom (i.e.,aNvacancy formation) followed by the oxidation of the freshly formed Ctermini.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…[29] Specifically,t he value of N (2C) /N (3C) in the RCN was only 0.2 lower than that of g-C 3 N 4 ,w hereasR CNO displayed av alue that was 1.00 lower;t his indicated that the pre-oxygenated treatment towards the g-C 3 N 4 prefers much the nitrogen vacancies formation during the H 2 reduction step, which was Table 2). The XPS spectra of O1s in g-C 3 N 4 andR CN showed a peak at the binding energy of 531.85 eV,w hich was attributed to the Oa toms in the NÀCÀOÀHm oiety.T he O1s peak in the RCNO sample was shifted to al ower binding energy of 531.36 eV,w hich corresponds to the formation of the C (3C) ÀNÀ Of unctionalg roup; [26] furthermore,anew peak appeared at 533.28 eV,w hich represented the Oa tom in C=Oo rC ÀO groups [30] and should be relatedt ot he release of the Na tom (i.e.,aNvacancy formation) followed by the oxidation of the freshly formed Ctermini.…”
Section: Resultsmentioning
confidence: 96%
“…This phenomenon implies that the interplanar spacing of the crystal decreased after oxidation, which intensifies the interaction between the g ‐C 3 N 4 crystal layers. This was attributed to the fact that the electronegativity of the O atom is greater than that of N and C atoms . The diffraction peak at 13.1° is the characteristic peak of crystal face (100) of the inplane repetition of tri‐ s ‐triazine units, which corresponds to a unit cell length along the c ‐axis of 0.68 nm .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A decrease of the PL intensity from g‐C 3 N 4 synthesized at high temperatures (>575 °C) is usually related to the formation of structure defects, which can capture charge carriers and cause the increased non‐radiative recombination rates and shorter lifetime of the carriers . Here, PL quenching presumably caused by in situ O‐doping of g‐C 3 N 4 facilitates charge separation …”
Section: Discussionmentioning
confidence: 99%